Improvement of Pempek Production Skills for People of Javanese Descendants in Sumber Rahayu Village, South Sumatera - Sari MZ, Rika Puspita (Journal of Saintech Transfer, 2022)
Pempek is a food that contains a lot of protein from fish meat in the form of a homogeneous protein gel, white in color, chewy and elastic texture. Improvement of pempek production skills for people of Javanese descendants in sumber Rahayu Village, south sumatera can to be a provision for the community as a side-home business in the midst of economic difficulties due to the Covid 19 pandemic. The methods in this activity are survey to get 15 person participants, pre-test and post-test of knowledge participant, discussion, demonstration producing of pempek and organoleptic test. Before training, a number of 53.8% of participants had ever made pempek and 38.5% of participants had knowledge about nutritional value of pempek. The average pre-test score is 38 points while the post-test score is 96 points. This shows that there is an increase in the knowledge and abilities of participants before and after being given the training. The average participant's assessment of the color, taste, and aroma of pempek is between 2.54 - 2.67. This shows that the participants like the color, taste, and aroma of pempek.